Spotlight on the psychological basis of childhood pet attachment and its implications - Wanser, Shelby H (Psychol Res Behav Manag, 2019)
Research suggests that humans can form strong attachments to their pets, and at least some pets display attachment behaviors toward their human caretakers. In some cases, these bonds have been found to support or enhance the physical and emotional well-being of both species. Most human–animal interaction research to date has focused on adult owners, and therefore less is known about childhood pet attachment. However, there is growing evidence that pets may play an important role in the development and well-being of children, as well as adult family members. Research conducted to date suggests that child–pet relationships may be especially impactful for children who do not have stable or secure attachments to their human caretakers. However, given that human–animal interactions, including pet ownership, can also introduce some risks, there is considerable value in understanding the nature of child–pet attachments, including the potential benefits of these relationships, from a scientific perspective. The purpose of this review is to provide background and a brief overview of the research that has been conducted on childhood attachment to pets, as well as to identify areas where more research would be beneficial.